Determinants of Youth Disengagement from Agricultural Opportunities in Rural: Evidence from Mbinga and Nyasa Districts, Ruvuma Region, Tanzania - Fokas Mbunda (Journal of Social and Community Development, 2026)
Youth disengagement from agriculture poses a critical challenge to rural development in Tanzania, limiting innovation, productivity, and the sector’s potential to support livelihoods. This study investigates the determinants of youth disengagement from agricultural opportunities in Mbinga and Nyasa Districts, Ruvuma Region, using a qualitative case study design. Data were collected through focus group discussions with 60 youth participants and 4 key informant interviews with four agricultural extension officers and community development officers. The study is anchored in the Theory of Reasoned Action and the Sustainable Livelihoods Framework to examine how individual attitudes, social norms, and structural factors influence youth decisions regarding agricultural engagement. Findings reveal that multiple intersecting factors shape youth disengagement. Agriculture is perceived as labor-intensive, low-reward, and socially unattractive, while economic constraints—such as limited access to capital and inputs and unstable markets—further reduce participation. The availability of alternative non-farming livelihoods, including bodaboda riding, petty trade, and casual labor, draws youth away from farming by offering immediate and reliable income. Institutional support, including loans, subsidies, and extension services, is underutilized due to information gaps and bureaucratic hurdles. The study concludes that addressing youth disengagement requires holistic interventions that improve economic incentives, enhance institutional support, and shift social perceptions of agriculture. Targeted policies and programs that integrate these dimensions can promote youth participation, strengthen rural livelihoods, and contribute to sustainable development in rural Tanzania.